Research on policies to promote scienctific and technological advances in the Northern mountainous agricultural production - Tuan, Tran Anh; Hang, Truong Thu (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
Over the years, Vietnamese agriculture has been growing at a rapid rate. However, recent growth rate tends to slow down, efficiency is not high and unsustainable. To further promote the role of agriculture in the economy, the Government has directed the implementation of the policy of restructuring the agricultural sector in association with the new rural construction. The most important solution to implement this policy is to accelerate the application and transfer of scientific and technological (S&T) advances, including high technology. In recent years, the Party and State have paid much attention to invest in the application and transfer of S&T advances in agriculture. The system of research and transfer organizations has been strengthened, human resources have been trained, and there have many innovative policies. However, in the face of the development needs of sector, efforts should be made to further promote policies to facilitate the development of application and transfer of S&T advances and to promote the role of system of institutions, universities, agricultural expansion systems, especially to encourage the participation of enterprises. This paper is intended to provide an overview of policy for the application and transfer of S&T advances in agriculture and to provide solutions to further promote the application and transfer of S&T advances for agricultural development in Northern mountainous area. Code: 17052401